Farmasi untuk Rakyat: Edukasi Kesehatan dalam Upaya Preventif Gastritis di Watugolong - Amarullah, Adinugraha; Setyawati, Herni; Anwari, Farida; Ramadhan, Achika Sardiah; Wahyudi, Denis Riskina; Wati, Fitri Indah (Conscilience: Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Gastritis is a condition characterized by inflammation of the gastric mucosa, which can lead to various complications if not properly managed. The prevalence of gastritis in Indonesia is relatively high, primarily due to irregular eating habits and a lack of public awareness about disease prevention. This outreach activity aimed to increase public awareness and knowledge about gastritis through a pharmaceutical education program conducted in Watugolong Village, Krian District, Sidoarjo Regency. The method used involved interactive counseling sessions including lectures, leaflets/brochures, and presentations, followed by pre-tests and post-tests to measure the effectiveness of the education. The results showed an increase in public understanding of gastritis, with post-test scores rising by 20% compared to the pre-test. This demonstrates that pharmaceutical education can be an effective strategy to raise public awareness regarding gastritis prevention.